DRIFTING TO SOCIALLY-ORIENTED ECONOMY AND SUSTAINABLE DEVELOPMENT OF THE RUSSIAN ARCTIC: THE INPUT OF TECHNOLOGICAL MODERNIZATION - B. N. Porfiryev; V. N. Leksin (Модернизация, инновация, развитие)
Purpose: the research paper purports to substantiate the must and opportunity of consistent combination integration of the policies of technological modernization, transition to socially-oriented economy and sustainable spatial development as an imperative requirement of the Arctic zone of the Russian Federation (AZRF) re-development.Methods: research methodology and methods employ interdisciplinary approach which integrates specific tools of research of economic, sociological, political science, ecological, legal and other issues of spatial systems’ functionings.Results: the obtained research results reveal that provided for budget constraints, volatility of hydrocarbon prices, ongoing international confrontation, climate change and other external and internal challenges socially and ecologically oriented technological modernization should become a priority of the AZRF state (public) and corporate policies. The issues of technological modernization should be tackled and solved concurrently with those of healthcare and supporting of the working capacity of industrial personnel, and reduction of the risk to local environment and communities. Case studies illustrating successful implementation of the above policies in the mining and energy sectors in selected AZRF regions are introduced.Conclusions and relevance: substantiated is the conclusion of imperative of the public policy stimulating socially and ecologically oriented technological modernization in the AZRF. Implementation of this policy should be preceded by the exhaustive inventory (survey) of the technical condition of each and every industrial, civil engineering and social infrastructure facility to reveal critical elements (areas) of technological obsoleteness and deterioration and provide assessment of the amount and sources of the resources necessary for the early (urgent) phase of technological modernization. Whatever the issue is considered the proposed solution should involve a full-fledged investment project which is a complex but solvable task of the modern state governance.